Breaking through the Sexed Glass Ceiling: Women in Academic Leadership Positions - Sheila Smith McKoy; Dawn Michelle Banauch; Keisha Love; Susan Kirkpatrick Smith (Academic Chairpersons Conference Proceedings, 2018)
In 2009, Patterson, Kirschke, Seaton and Hossfeld revisited the ongoing conversation about gender inequity and inequality in higher education. Their work entitled Challenges for Women Department Chairs (New Prairie Press, 2009) focused on the numerous gaps – salary, promotion, discrimination, harassment -- that define women’s experiences in academic leadership. The emerging trends in academia still suggest that the work that they started in 2009 continues to be a vital concern for women in academic leadership positions. Very little research exists in relation to the intersectional conversations that need to occur when these gendered gaps are coupled with other aspects of difference including age, appearance, race, field and ethnicity. In spite of the lack of research focused on the intersections among aspects of difference as they relate to women in academic leadership, the lived experiences of women academic leaders is defined by both covert overt acts of gender-based and intersectional discrimination that is deeply entrenched in the academy. As women rise in the ranks of academic leadership, it is critical for women in academic leadership positions to address this entrenchment by exposing the multiple axes of this bias and by incorporating real-world solutions to the problems that we face. As importantly, this entrenchment has been complicated by the ways in which the current political climate has impacted the work of the university in reference sexism, racism and the risk of campus carry initiatives. Women serving in leadership roles at the college level, provost level and as department chairs – arguably one of the most difficult positions in academia – must advocate for their own work as academic leaders while simultaneously continuing to expand their administrative and research profiles. In this seminar, participants will have the opportunity to evaluate, discuss and respond to real-life scenarios focused on women in academic leadership. The panelists will frame the discussion by presenting an extensive literature review, relevant data and experience-driven solutions so that presenters will leave the panel with a heuristic through which to derive solutions for the issues that women leaders in academia face. Participants will have the opportunity to review case studies and derive real-world solutions to the problems that women leader face in academia.
Keywords: women; academic leadership; diversity; inclusion; mentoring